2023
DOI: 10.32523/ejpfm.2023070102
|View full text |Cite
|
Sign up to set email alerts
|

Electron-hole trapping centers in Na2SO4 with a transition metal impurity Mn

Abstract: The Na 2 SO 4 samples were obtained by slow evaporation method. The mechanisms of the formation of electron and hole trapping centers are investigated by spectroscopic methods. Intrinsic recombination emission of 2.9-3.1 eV and impurity emission of 1.85 eV are excited at 4.0-4.5 eV. Intrinsic SO 3− 4 − SO − 4 and impurity Mn + − SO − 4 trapping centers were revealed. The local levels corresponding between the electron and hole trapping center are 4.0-4.5 eV. The decay of intrinsic and impurity trapping centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The authors of [18][19][20] studied the mechanisms of energy transfer to impurities in alkali metal sulfates, in activated CaSO 4 -Mn and Na 2 SO 4 -Cu crystals. The excitation spectra of impurities and intrinsic recombination emissions of the host were measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [18][19][20] studied the mechanisms of energy transfer to impurities in alkali metal sulfates, in activated CaSO 4 -Mn and Na 2 SO 4 -Cu crystals. The excitation spectra of impurities and intrinsic recombination emissions of the host were measured.…”
Section: Discussionmentioning
confidence: 99%
“…At photon energies between 6 and 12.4 eV, free electron-hole pairs are formed, which results in the formation of these recombination emissions. It has been experimentally shown that, upon excitation in the recombination emission bands at 3.0-3.1 eV and 2.6-2.7 eV, excitations appear corresponding to 3.9-4.0 eV and 4.45-4.5 eV [17][18][19][20] in the transparency region of the host. These excitation energies must correspond to the local levels of electron SO 3− 4 and hole SO − 4 trapping centers.…”
Section: Introductionmentioning
confidence: 99%